Investigating the Efficacy of L-Arginine and Aged Garlic Extract in a Randomised Place-Controlled Clinical Trial: A Vasodilatory Nutraceutical Strategy for Migraine Prevention - Chaliha, Devahuti Rai (Curtin University, 2024)
While studies imply it is cerebral vasodilation that triggers migraine pain onset, we suggest the carbon-dioxide-inducing vasodilation rescues migraine phenotype by restoring central capillary perfusion instead. We conducted a 12-week, phase-II, single-site, randomised, double-blind, parallel-group, placebo-controlled trial in male and female adults with chronic frequent episodic migraines (4 treatment arms: placebo, L-arginine, aged garlic extract (AGE), and L-arginine + 1 g AGE). The descending order of efficacy was as follows: L-arginine, then AGE, then combination.